2016
DOI: 10.4103/0301-4738.190099
|View full text |Cite
|
Sign up to set email alerts
|

Adult onset retinoblastoma

Abstract: Retinoblastoma (RB) is the most common primary malignant intraocular tumor of childhood presenting usually before 5 years of age. RB in adults older than 20 years is extremely rare. A literature search using PubMed/PubMed Central, Scopus, Google Scholar, EMBASE, and Cochrane databases revealed only 45 cases till date. Over the past decade, there has been a significant increase in the number of such reports, indicating heightened level of suspicion among ophthalmologists. Compared to its pediatric counterpart, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 44 publications
2
6
0
Order By: Relevance
“…Smaller, more peripheral tumors could be less symptomatic and less easily visualized on funduscopic examination, resulting in delay in diagnosis and treatment in these patients. This is consistent with prior series of adult RB, which reported a mean duration of symptoms before diagnosis of 12–15 months 6, 13. Insidious symptoms in older-onset and adult RB patients can result in loss of considerable time before seeking ophthalmic consultation, which might explain the preponderance for group D (30%) and E (65%) eyes in this study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Smaller, more peripheral tumors could be less symptomatic and less easily visualized on funduscopic examination, resulting in delay in diagnosis and treatment in these patients. This is consistent with prior series of adult RB, which reported a mean duration of symptoms before diagnosis of 12–15 months 6, 13. Insidious symptoms in older-onset and adult RB patients can result in loss of considerable time before seeking ophthalmic consultation, which might explain the preponderance for group D (30%) and E (65%) eyes in this study.…”
Section: Discussionsupporting
confidence: 92%
“…In a series of older RB patients by Shields et al, subjective symptoms such as decreased vision (35%) were found to be more common than objective findings of leukocoria (35%) and strabismus (15%) 5 . In our study, leukocoria (51%), decreased vision (26%), and strabismus (9%) were the most common presenting findings, although we observed a decreased prevalence of leukocoria ( p < 0.01) and strabismus ( p = 0.1) with age, consistent with prior reports 5, 13. Moreover, atypical signs of RB, including hypopyon, anterior chamber cells simulating uveitis, and/or vitreous hemorrhage, are known to occur more frequently in cases of late-onset RB and often lead to misdiagnosis with delayed treatment (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…[ 9 10 ] Histopathology of the enucleated specimen in the majority of the reported adult retinoblastoma cases had differentiated, showing Flexner-Winter Steiner rosettes. [ 6 11 ] In our case, the tumor was classified as undifferentiated retinoblastoma with no rosettes and fleurettes with massive necrosis and hemorrhage. In conclusion, although retinoblastoma in general is rare among adult population, it should be considered in the differential diagnosis of sudden onset intraocular mass with unusual clinical presentation in Saudi adults.…”
Section: Discussionmentioning
confidence: 73%
“…[ 1 ] Adult-onset retinoblastoma is extremely rare and hence is usually not considered in the top differential diagnosis of adults presenting with retinal or intraocular lesions. As per literature review, only 45 cases was reported till date[ 2 3 4 5 6 ] and the oldest report was presented in 1919 from a 20-year-old white girl. [ 2 ] The oldest reported age of RB in the Saudi population was 12 years.…”
Section: Introductionmentioning
confidence: 99%